The Students’ Perception on Academic Reading Log for Essay Writing Literacy: Some Influential Points: Persepsi Siswa tentang Academic Reading Log untuk Literasi Penulisan Esai: Beberapa Poin yang Berpengaruh - Rahmawati, Henny; Sholihah, Fitri Awaliyatush (JEES (Journal of English Educators Society), 2019)
Reading log or the so-called reading journal is a journal to monitor how far the students read within their own pace and time. This study aimed at investigating some influential points of using reading log in order to enhance the students’ ability in writing academic article. The participants of this study were twenty sophomores pursuing their study at Universitas Islam Malang taking Writing IV class. They were asked to fill reading logs given after reading academic articles. They had to read one academic article each day for one week. Questionnaire and interview were used as the instruments to collect the data which were then analyzed descriptive qualitatively. The findings show that reading log is very beneficial for the students specifically when they are reading academic articles.